Penerapan Metode Diskusi Terhadap Peningkatan Hasil Belajar PAI di Kelas X.E.4 SMA Negeri 8 Padang - Ahsani Taqwyma (Jurnal Pendidikan Tuntas, 2024)
This study aims to determine the effectiveness of implementing the discussion method in improving Islamic Religious Education (PAI) learning outcomes in class X.E.4 at SMA Negeri 8 Padang. This research employs a Classroom Action Research (CAR) approach consisting of four cycles: planning, action, observation, and reflection. The results show that the discussion method can enhance students' understanding of the subject matter and their involvement and confidence in expressing opinions. In the first cycle, the percentage of student learning completeness was 60%, which increased to 80% in the second cycle and reached 100% in the third cycle. With effective teacher guidance and well-prepared planning, this method can serve as an innovative and effective learning strategy.